Spontaneous nano-gap formation in Ag film using NaCl sacrificial layer for Raman enhancement - Min, Kyungchan; Jeon, Wook Jin; Kim, Youngho; Choi, Jae Young; Yu, Hak Ki (Nanotechnology, 2018)
We report the method of fabrication of nano-gaps (known as hot spots) in Ag thin film using a sodium chloride (NaCl) sacrificial layer for Raman enhancement. The Ag thin film (20-50 nm) on the NaCl sacrificial layer undergoes an interfacial reaction due to the AgCl formed at the interface during water molecule intercalation. The intercalated water molecules can dissolve the NaCl molecules at interfaces and form the ionic state of Na+ and Cl-, promoting the AgCl formation. The Ag atoms can migrate by the driving force of this interfacial reaction, resulting in the formation of nano-size gaps in the film. The surface-enhanced Raman scattering activity of Ag films with nano-size gaps has been investigated using Raman reporter molecules, Rhodamine 6G (R6G).
Keywords: Hot spot; Intercalated water; NaCl; Raman enhancement; Reporter molecules; SERS; Sodium chloride (NaCl); Surface enhanced Raman Scattering (SERS); Ag hot spot; NaCl; Raman enhancement; SERS